1998
DOI: 10.1021/np980319l
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Structure Revision of Pepluane Diterpenoids from Euphorbia peplus

Abstract: A new pepluane diterpene polyester (2) was isolated from a CH2Cl2 extract of the whole, undried plant of Euphorbia peplus, together with the known compound 1. The structures were established by high-field spectroscopic methods, including 2D NMR techniques, and by X-ray crystallography, and the stereostructure of the first member of the pepluane diterpenoids (1) was revised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 4 publications
0
34
0
Order By: Relevance
“…36 A conformational study showed that pepluane possesses a relatively rare ring D conformation, which probably led to the misinterpretation of the NMR data. 36 The challenging 3D determination of some jatrophane esters may also be exemplified by a study by Hohmann and associates, in which the relative configuration of esulatin C could not be assigned. 34 The high flexibility of the macrocyclic part of this compound was one of the explanations made.…”
mentioning
confidence: 99%
“…36 A conformational study showed that pepluane possesses a relatively rare ring D conformation, which probably led to the misinterpretation of the NMR data. 36 The challenging 3D determination of some jatrophane esters may also be exemplified by a study by Hohmann and associates, in which the relative configuration of esulatin C could not be assigned. 34 The high flexibility of the macrocyclic part of this compound was one of the explanations made.…”
mentioning
confidence: 99%
“…The acetylated vicinal diol (C-8 and C-9) found in all known pepluans, can be explained by an enzymatic epoxidation in D8(9) followed by an opening of the epoxide as shown in Fig. 11 (Hohmann et al 1999a;Jakupovic et al 1998c).…”
Section: Pepluane and Paralianementioning
confidence: 96%
“…The results showed the importance of functionality and structure of the D-ring for the activity and its possible involvement in the inhibition of NF-jB activation as follows ( compounds exhibited inhibitory effects on LPSinduced NO production which possessed lipophilic substituents such as benzoyl, nicotinoyl and decadienoyl moieties with IC 50 values ranging from 0.7 to 46.5 lM in RAW 264.7 macrophages (Lee et al 2016). Wan et al (2016a, b) isolated paralianones A-D (66-69) and pepluanols A-H (52-56, 58, 62, and 63), along with five known compounds 72 (Jakupovic et al 1998b), 59 (Hohmann et al 1999a), 60 (Hohmann et al 2000a), 61 (Hohmann et al 1999b), and pepluanone (57) (Corea et al 2005b), from E. peplus.The isolated compounds were tested for inhibitory activity on LPS-stimulated NO production in RAW264.7 macrophage cell line. Compounds 68, 69, 62, 72, and 61 displayed inhibitory effects on NO inhibition, with IC 50 values of 33.7, 38.3, 36.6, 29.9, and 37.1 lM, respectively.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…The phytochemical investigation of E. peplus was started in our department in 1999, and 13 diterpenes ( 9 , 12 , Figure 3; 20 – 27 , 30 – 32 , Figure 5) with different skeletons (pepluane, jatrophane and ingenane) were isolated from the whole plant 2,57,58. Three diterpenes ( 20 – 22 ) have a pepluane skeleton and differ only in the esterification.…”
Section: Isolation Of Diterpenesmentioning
confidence: 99%
“…In the pepluanes, the geminal dimethyl groups (originating from a cembrene‐casbane source) are absent, because one of them (C‐18) is incorporated in a six‐membered ring. On the basis of our X‐ray examinations, the structure of 20 was revised with regard to the absolute stereochemistry at C‐8 and C‐9 57…”
Section: Isolation Of Diterpenesmentioning
confidence: 99%